2016
DOI: 10.1016/j.compstruct.2016.02.074
|View full text |Cite
|
Sign up to set email alerts
|

Resin treatment of free edges to aid certification of through thickness laminate strength

Abstract: Large aerospace parts are typically certified by testing narrow specimens, such as curved laminates, which have exposed free edges. These edges (not present in the production part) have been found to reduce the 3D strength of curved laminates by over 20%, showing this certification method is unreasonably conservative. The free edges also create a singularity, such that Finite Element (FE) modelling is challenging, which is typically approximated using non-linear analysis of cohesive interlaminar zones. A new t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 19 publications
4
31
0
Order By: Relevance
“…al. have shown that the Camanho failure criterion predicts failure to within 5% of average experimental test values [16] with treated edges to mitigate premature failure. Here, for simplicity, we discount the edge effects by not evaluating the failure criterion close to the boundary to isolate the effects of wrinkles.…”
Section: Finite Element Modellingmentioning
confidence: 98%
See 4 more Smart Citations
“…al. have shown that the Camanho failure criterion predicts failure to within 5% of average experimental test values [16] with treated edges to mitigate premature failure. Here, for simplicity, we discount the edge effects by not evaluating the failure criterion close to the boundary to isolate the effects of wrinkles.…”
Section: Finite Element Modellingmentioning
confidence: 98%
“…The plies were assumed to have a thickness of 0.24 mm, with a 0.015 mm interface layer of pure resin between each ply. This is based upon measurements taken from micrograph images of the curved laminates as described by Fletcher et al [16]. The assumed mechanical properties for both the fibrous ply material and the resin rich interface material are given in Section 3.4.…”
Section: Finite Element Modellingmentioning
confidence: 99%
See 3 more Smart Citations